Pseudomonas fluorescens and Pseudomonas putida for Promoting Growth of Jatropha curcas Seedling Root - Sri Sumarsih; Darban Haryanto (Journal of Tropical Life Science, 2012)
Pseudomonas fluorescensandP. putida are Plant Growth Promoting Rhizobacteria (PGPR) that can produce growth hormone. The objective of this study is to know the effects of those two combined species of PGPR on seedling root growth of Jatrophacurcas. The condition of the seedling root determines the success of dry land cultivation. The root which has wider coverage, is larger in number, and is bigger in diameter makes seedling more resistant to stress in dry land environment. In the experiment, two kinds of plant materials are used for seedling, the Jatropha seed and stem material, which are treated in a mixed culture of PGPR. For the Jatropha seed, this mixed culture of PGPR is given at the same time of cultivating the sprout on the seedling medium. For the stem cutting, the PGPR is poured in together during the first watering of the seedling cultivation medium. In the fourthweek, the observed growth parameters are root length, root diameter, primary and secondary lateral root numbers, Root Length Density (RLD), Frequency of Lateral Root (FLR), and Specific Root Length (SRL). These data are analyzed using analysis of variant with DMRT test at 0.05 level of significance. The result of this study shows that PGPR tend to reduce FLR values on the seedling root made from seeds. On the seedling root made from stem cutting, PGPR increase the root length, primary and secondary lateral root numbers, root diameter, FLR and SRL values as well. Keywords: Pseudomonas, PGPR, root, Jatropha